2013
DOI: 10.12717/dr.2013.17.3.221
|View full text |Cite
|
Sign up to set email alerts
|

Expression Analysis of Cathepsin F during Embryogenesis and Early Developmental Stage in Olive Flounder (Paralichthys olivaceus)

Abstract: Cathepsins are members of the multigene family of lysosomal cysteine proteinases and have regulated function in several life processes. The potential role of cathepsin F cysteine gene was expected as protease in the yolk processing mechanism during early developmental stage, but expression analysis was unknown after fertilization. The alignment analysis showed that amino acid sequence of cathepsin F from olive flounder liver expressed sequence tag (EST) homologous to cathepsin F of other known cathepsin F sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…(3) Cathepsin F, which is a member of the multigene family of lysosomal cysteine proteinases, that has regulatory roles in several homeostasis processes (Lee et al, 2013); (4) CYP8B1, which plays an important role in the synthesis of cholesterol and bile acids (Lorbek et al, 2012); (5) FMO2; (6) FMO5, which are members of the flavin-containing monooxygenase (FMO) gene family, which oxidize a variety of soft nucleophilic substrates (Mccombie et al, 1996); (7) THRB, which is a thyroid hormone receptor (THR) that mediates thyroid hormone action; (8) UGT1A1, which is an enzyme on the glucuronidation pathway; studies have indicated that polymorphisms in its promoter are associated with various diseases and drug responses (Shin et al, 2015); (9) TLR5. Which encodes a member of the toll-like receptor (TLR) family playing fundamental roles in pathogen recognition and activation of innate immune responses; and (10) UGT2A1, which encodes an enzyme in the glucuronidation pathway; it transforms small lipophilic molecules such as steroids and drugs into water-soluble, excretable metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…(3) Cathepsin F, which is a member of the multigene family of lysosomal cysteine proteinases, that has regulatory roles in several homeostasis processes (Lee et al, 2013); (4) CYP8B1, which plays an important role in the synthesis of cholesterol and bile acids (Lorbek et al, 2012); (5) FMO2; (6) FMO5, which are members of the flavin-containing monooxygenase (FMO) gene family, which oxidize a variety of soft nucleophilic substrates (Mccombie et al, 1996); (7) THRB, which is a thyroid hormone receptor (THR) that mediates thyroid hormone action; (8) UGT1A1, which is an enzyme on the glucuronidation pathway; studies have indicated that polymorphisms in its promoter are associated with various diseases and drug responses (Shin et al, 2015); (9) TLR5. Which encodes a member of the toll-like receptor (TLR) family playing fundamental roles in pathogen recognition and activation of innate immune responses; and (10) UGT2A1, which encodes an enzyme in the glucuronidation pathway; it transforms small lipophilic molecules such as steroids and drugs into water-soluble, excretable metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Most mature miRNA sequences are conserved across amphibians, fish, and mammals (Kloosterman & Plasterk, ). Recently, miRNA expression has also been examined in the gonads of fish and mammals, such as allotetraploid hybrid fish and Carassius auratus (Zhou et al, ), P. fulvidraco (Cao et al, ), O. niloticus (Xiao et al, ), P. olivaceus (Lee et al, ), primates (Yan et al, ), and mice (Reid et al, ), using next‐generation sequencing technologies. These studies show that miRNAs are very important for sex differentiation and gonadal development.…”
Section: Introductionmentioning
confidence: 99%